About friendship of poet-veterinarian О. Оles with family of М. Choromansky - S. K. Rudyk; O. G. Мoldovan (History of science and technology, 2013)
For the first time is given historical information about influence of О. Оles on creativity of the Polish writer М. Choromansky.